Літературні портрети І. Франка й Лесі Українки в критиці Є. Маланюка - Краснощок, Вікторія Валеріївна (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті систематизовано роздуми Євгена Маланюка, спрямовані на багатогранне осмислення постатей Івана Франка й Лесі Українки, творчі набутки котрих стали яскравим втіленням феномену «національного інтелекту». Проаналізовано концепти Маланюка стосовно діалектики раціонального й емоційного начал творчості цих митців, превалювання контролю думки над чуттєвістю. Здійснено наближення до розуміння феномену «аристократизму» та «елітарності» в їхній художній творчості. The article systematized Malaniuk’s thinking aimed at understanding the multifaceted personalities Ivan Franko and Lesia Ukrainian, creative achievements of which played an embodiment of the phenomenon of «national emotion» and “national intelligence». The researcher found that the work of these writers inherent intellectual and emotional understanding of being. Malaniuk determines biographical facts, moments that contributed to the crystallization of the philosophical vision of reality: Franko’s ideological break, feeling disappointment in the ideals that realized in the artistic image of the leader of the nationʼs model; first drama love of Lesi Ukrainian has stimulated its reflexivity and philosophical, postulated a «three-dimensional» perception of being the motive of chivalry. Analyzed in relation to concepts Malaniuk’s dialectic principles of rational and emotional work of these artists, the prevalence of control over thoughts sensuality. Realized approach to understand the phenomenon of «gentility» and «elitism» in their artistic creativity.
Keywords: Іван Франко; Леся Українка; есеїстика Євгена Маланюка; націоцентризм; художній талант; творча елітарність